Outcome of conjunctival autograft sutured with polyamide black sutures in pterygium surgery - Kavitha, CV (Nepalese Journal of Ophthalmology, 2013)
Introduction: Pterygium excision with conjunctival autografting is the most effective way of treating pterygium with the least recurrence rate. The sutures which can be used to suture the conjunctival autograft are absorbable polyglactin 10-0 sutures or nonabsorbable polyamide 10-0 sutures. The polyamide sutures are inert, elicit minimal acute inflammatory reaction, do not support infection and allow easy removal without tissue adherence. They are very cost-effective compared to polyglactin sutures. Objective: This study was aimed to assess the efficacy of the cost-effective polyamide sutures in terms of patient comfort, graft stability, need for suture removal and recurrence. Materials and methods: In this prospective, non-comparative study, 56 eyes of 56 patients with primary pterygium underwent pterygium excision with conjunctival autograft transplantation sutured with 10-0 polyamide black sutures. The patients’ comfort, graft stability, need for suture removal and recurrence were assessed within a mean follow- up period of 28.75 months (range 47 - 14 months). Results: Mild discomfort was found in 14 (25 %) patients for up to 3 weeks, moderate discomfort in 8 (14.2 %) for up to 1 week, no patients had severe discomfort beyond the first day, and all patients were comfortable at the end of the sixth post-operative week. The graft was stable in all patients. Nine sutures in 5 patients out of 392 sutures in 56 patients, that is, 2.29 % of the sutures, needed to be removed at the end of the sixth post-operative week. Two patients, or 3.57 %, had a recurrence. Conclusion: In pterygium surgery, suturing the conjunctival autograft with cost-effective polyamide black sutures is efficient and safe. Nepal J Ophthalmol 2013; 5(9):94-99 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7833